Squamous cell carcinoma arising from an unknown primary site metastasizing to the stomach: A case report - WANG, GUANGYAO (D.A. Spandidos, 2014)
Primary squamous cell carcinoma (SCC) may originate elsewhere in the body, including the head, neck, lung, bronchus, cervix uteri, esophagus and cardia, and metastasize to the stomach. In the present report, a case is presented of an SCC, which arose from an unknown primary site and metastasized to the stomach of a 59-year-old male. The tumor was located in the interspace between the liver and the stomach. It involved the placenta percreta, lamina muscularis and submucosa, however, had already metastasized to a regional lymph node at the time of surgery. No SCC was observed in other organs on physical examination, which included positron emission tomography-computed tomography. In the follow-up period, there was no evidence of additional malignant tumors in the patient; therefore, the origin of the tumor was speculative. To the best of our knowledge, this is the first case report regarding a tumor of this type.